SYSTEM OF GENERALIZED HIERARCHICAL VARIATIONAL INEQUALITY PROBLEMS - Salahuddin (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2019)
In this study, we discussed the solution of a system of generalized hierarchical variational inequality problems in Hilbert spaces by using the concepts of Mainge’s. We also discussed some applications.